Den Text wie eine Frucht verspeisen. Zhu Xi (1130–1200) über das rechte Lesen - Lackner, Michael (Poetica, 2023)
In addition to his numerous commentaries on the Confucian classics and his treatises, the eminent Chinese philosopher Zhu Xi (1130–1200) also left a large number of statements on learning. These reflections were collected by later scholars of his school under the title “Master Zhu on Learning” (Zhuzi dushufa). This article is based on the original texts in “Master Zhu’s Collected Sayings” (Zhuzi yulei), an encyclopedic compilation of the master’s responses to questions from his students. Zhu Xi deals with the appropriate syllabus (“what to read first”), but especially with the methods for proper reading (“how to read”). Emphasis is placed on the use of metaphors from the world of the senses, such as “eating,” “swimming,” “gardening,” “eyeing a house,” etc. In a final section, a somewhat unconventional – but still serious – attempt is made to compare Martin Luther’s Table Talks (Tischreden) and his mixture of Latin and German with Zhu Xi’s use of the classics in his explanations.
CRIS-Team Scopus Importer:2025-07-10